If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 1.5X = 10 + X Solving 6 + 1.5X = 10 + X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 6 + 1.5X + -1X = 10 + X + -1X Combine like terms: 1.5X + -1X = 0.5X 6 + 0.5X = 10 + X + -1X Combine like terms: X + -1X = 0 6 + 0.5X = 10 + 0 6 + 0.5X = 10 Add '-6' to each side of the equation. 6 + -6 + 0.5X = 10 + -6 Combine like terms: 6 + -6 = 0 0 + 0.5X = 10 + -6 0.5X = 10 + -6 Combine like terms: 10 + -6 = 4 0.5X = 4 Divide each side by '0.5'. X = 8 Simplifying X = 8
| c+54=51 | | s^2+9=6s | | 6p-101=7 | | 4n-40=7(-2n+4) | | 8x-3=15.2 | | s^2-7s=0 | | 49c^2-16=0 | | -6n-2=-2n+4(1-3n) | | -10x-11=-131 | | (x+4)=(x+3) | | -2(3n+8)=-12 | | 5x+20=(x-2)+21 | | -12p-4(2-5p)=5(p-3)-2 | | 3x-3=(x-2)+7 | | 8y-4x=32 | | 6x^2+19x-69=0 | | .005(x+2)=.006x+.006 | | 5y-4x=32 | | x^2=5(x-100) | | .25x+.05(14-x)=.10(-9) | | 7x-4x=x+6 | | 2x+8=98 | | 36-3x=4+x | | 12x+3=2(3x+1)-x+9 | | -2(z-4)-(3z-2)=-2-(6z-2) | | 36-3x=4x | | -x+3+9x=-3+2x+12 | | 6x^2+13x-26=0 | | 28(3x-4)+28(x+3)=28*8 | | 7x+3=19+3x | | 2x^2+3x-90=0 | | x+9y=2 |